The influence of triglycerides on small dense low‐density lipoprotein cholesterol levels is attenuated in low low‐density lipoprotein‐cholesterol range: Implications for the negative results of the PROMINENT trial - Tsutomu Hirano; Yasuki Ito (Journal of Diabetes Investigation, 2023)
Abstract The Pemafibrate to Reduce Cardiovascular Outcomes by Reducing Triglycerides in Patients with Diabetes (PROMINENT) trial failed to show the preventive effects of pemafibrate, a triglyceride (TG)‐lowering drug, on atherosclerotic cardiovascular disease in patients with type 2 diabetes and dyslipidemia. We recently reported that TG‐lowering with pemafibrate did not decrease the calculated small dense (sd) low‐density lipoprotein cholesterol (LDL‐C), and speculated that the effect of TG on sdLDL‐C is attenuated in low LDL‐C levels. This report examined this possibility in 1,508 patients with type 2 diabetes and 670 healthy controls. LDL‐C ranges were classified as ≤69, 70–99, 100–139 and 140≤ mg/dL. The slope of the regression curve between sdLDL‐C and TG was found to flatten as LDL‐C decreased; 0.18, 0.13, 0.10 and 0.04 for controls, and 0.18, 0.13, 0.09 and 0.07 for diabetes patients. Correspondingly, the lower the LDL‐C range, the lower the sdLDL‐C/TG ratio. These results suggest that when LDL‐C is tightly controlled, TG‐lowering has only a weak inhibitory effect on sdLDL‐C.